(untitled) (Fiep Bulletin - online, 2014)
The present study aimed to diagnose and to analyze the perception of recently-formed of the area of physical education with relationship the damage liability in its future professional performance. They participated 20 recently-formed professionals of physical education of a public University in the city of Irati, State of Paraná. As instrument was used a questionnaire starting from themes selected as damage liability, its limits and duty of reimbursing. Considering referring subjects to the knowledge, compensation, subject of that duty and damage type, most of those questioned evidenced an almost total ignorance on the subject. This ignorance or partial knowledge of the legislation and the controversy existence, demonstrated in the answers, they take the recently formed to an understanding misunderstood concerning the theme, they demonstrated excessive concern with the financial subject, though without enough knowledge of the legal norms in order to prevent eventual occurrences, what can generate insecurity in these professionals, which feel unprotected in the face of the occurrence of eventual lawsuit.